Study of factors influencing the fabrication of Co‐porphyrin porous coordination polymer via metal–organic gel intermediate. (2nd September 2019) - Li, Jun; Zhao, Jiale; Cheng, Minglun; Yi, Jiajia; Yuan, Lin; Wang, Ning; Li, Jun
Abstract : In this work, 5, 10, 15, 20‐Tetra‐(4‐aminophenyl) porphyrin (TAPP) was used as gelator to prepare metal‐porphyrin porous coordination polymer (PCP) via solvothermal process, Soxhlet extraction and supercritical CO2 extraction. Firstly, the metal‐porphyrin organic gel (MOG) was prepared as intermediate with solvothermal method. The generation of gels is associated with many factors. When four acetates [Co(Ac)2 4H2 O, Zn(Ac)2 2H2 O, Mn(Ac)2 4H2 O and Ni(Ac)2 7H2 O] reacted with TAPP, only the reaction between Co(Ac)2 4H2 O and TAPP could form desired metal‐porphyrin organic gel. The influences of solvent, concentration and anions were investigated in the gelation process. Secondly, the residual reactants and solvent molecules in MOG were removed through Soxhlet extraction and supercritical CO2 extraction. The Co‐PCP is an amorphous material with a hierarchical porous structure can effectively catalyze the oxidation of ethylbenzene and also exhibits a strong adsorptive capacity for the strong‐polar solvent molecules. Abstract : A three‐step method was used to prepare metal‐porphyrin porous coordination polymer, containing solvothermal process, Soxhlet extraction and supercritical CO2 extraction. It was found that the solvent, metal ions, anions and concentration of the solution play important roles in the gelation process. Compared with drying in air, the Soxhlet extraction and supercritical CO2 extraction are efficient way to avoids the collapse of frame construction. The prepared metal‐porphyrin porous coordination polymer has potential application in catalysis and adsorption.